Positive experiences related to living with tinnitus: a cross-sectional survey - Beukes, Eldre W.; Baguley, David M.; Allen, Peter M.; Manchaiah, Vinaya; Andersson, Gerhard (Wiley, 2017)
Objective: The aim of this study was to gain insights related to positive experiences reported by adults with tinnitus living in the United Kingdom. Design: A cross-sectional survey design was used in a sample of adults with tinnitus who were interested in undertaking an Internet-based intervention for tinnitus. Setting: The study was UK wide and data collection was online. Participants: Participants consisted of 240 adults (137 males, 103 females), with an average age of 48.16 years and average tinnitus duration of 11.52 years (SD: 11.88). Main outcome measures: Tinnitus severity was measured by means of the Tinnitus Functional Index. To evaluate the secondary effects of tinnitus, the Insomnia Severity Index, the Hearing Handicap Inventory for Adults-Screening Version and the Cognitive Failures Questionnaires were administered. Positive experiences related to tinnitus were explored using an open-ended question format. Results: Around a third of participants (32.5%) reported positive experiences associated with tinnitus. The number of positive responses ranged from one to eight responses per participant, although there were fewer participants with more than one positive response. The predominant themes concerned for (i) coping; (ii) personal development; (iii) support, and to a lesser extent (iv) outlook. Younger participants, those with a lower hearing disability and those with fewer cognitive failures were more likely to report positive experiences associated with having tinnitus. Conclusions: This study has identified that personal development and a positive outlook are possible despite experiencing tinnitus. Ways to facilitate positive experiences related to tinnitus should be promoted, as these may reduce the negative consequences associated with tinnitus. The most prevalent positive theme was the ability to cope with tinnitus. Positive experiences were also drawn from having clinical and other support networks. This highlights the importance of providing tinnitus interventions that can assist people in coping with tinnitus, particularly to those less likely to relate tinnitus to any positive experiences. Those most likely to be helped include those who are older with greater cognitive difficulties and a greater hearing disability.